Modifying MSC Phenotype to Facilitate Bone Healing: Biological Approaches - Goodman, Stuart B.; Lin, Tzuhua (Frontiers in Bioengineering and Biotechnology, 2020)
Healing of fractures and bone defects normally follows an orderly series of events including formation of a hematoma and an initial stage of inflammation, development of soft callus, formation of hard callus, and finally the stage of bone remodeling. In cases of severe musculoskeletal injury due to trauma, infection, irradiation and other adverse stimuli, deficient healing may lead to delayed or nonunion; this results in a residual bone defect with instability, pain and loss of function. Modern methods of mechanical stabilization and autologous bone grafting are often successful in achieving fracture union and healing of bone defects; however, in some cases, this treatment is unsuccessful because of inadequate biological factors. Specifically, the systemic and local microenvironment may not be conducive to bone healing because of a loss of the progenitor cell population for bone and vascular lineage cells. Autologous bone grafting can provide the necessary scaffold, progenitor and differentiated lineage cells, and biological cues for bone reconstruction, however, autologous bone graft may be limited in quantity or quality. These unfavorable circumstances are magnified in systemic conditions with chronic inflammation, including obesity, diabetes, chronic renal disease, aging and others. Recently, strategies have been devised to both mitigate the necessity for, and complications from, open procedures for harvesting of autologous bone by using minimally invasive aspiration techniques and concentration of iliac crest bone cells, followed by local injection into the defect site. More elaborate strategies (not yet approved by the U.S. Food and Drug Administration-FDA) include isolation and expansion of subpopulations of the harvested cells, preconditioning of these cells or inserting specific genes to modulate or facilitate bone healing. We review the literature pertinent to the subject of modifying autologous harvested cells including MSCs to facilitate bone healing. Although many of these techniques and technologies are still in the preclinical stage and not yet approved for use in humans by the FDA, novel approaches to accelerate bone healing by modifying cells has great potential to mitigate the physical, economic and social burden of nonhealing fractures and bone defects.